2009
DOI: 10.1016/j.ymeth.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Tumor models and specific contrast agents for small animal imaging in oncology

Abstract: a b s t r a c tDespite the widespread use of various imaging modalities in clinical and experimental oncology without or with combined application of commercially available nonspecific contrast agents (CAs), development of tissue-or organ-or disease-specific CAs has been a continuing effort for pursuing ever-improved sensitivity, specificity, and applicability. This is particularly true with magnetic resonance imaging (MRI) due to its intrinsic superb spatial/temporal/contrast resolutions and adequate detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 76 publications
(154 reference statements)
1
51
0
Order By: Relevance
“…The rabbit model of VX2 liver metastasis was established by referring to the method of Ni et al [15]. Hepatic implantation of the VX2 carcinoma was accomplished under general i.v.…”
Section: Experimental Methods Of Animalsmentioning
confidence: 99%
“…The rabbit model of VX2 liver metastasis was established by referring to the method of Ni et al [15]. Hepatic implantation of the VX2 carcinoma was accomplished under general i.v.…”
Section: Experimental Methods Of Animalsmentioning
confidence: 99%
“…Thus, response to the same treatment may differ depending on tumor location and host-tumor interaction, because the organ-specific regulation of the balance between pro-and anti-angiogenic factors is responsible for the different angiogenesis activities [2,4,62,72] . As a result, tumor models of orthotopic transplantation into visceral organs of host animals with intact immune functions are thought to be more relevant to the conditions of clinical patients in terms of better mimicking tumor microenvironment, therefore, the treatment outcomes are more translatable into patients [62,72] . For imaging studies of VDA effects in small rodents, image quality has been shown to be satisfactory, even for organs susceptible to motion artifacts with nonrespiratory-gated acquisition at a clinical magnet [56] .…”
Section: Animal Tumor Modelsmentioning
confidence: 99%
“…1D of the article by Narita et al [1] is to date the closest clinical finding comparable to what has been reported in rats [3,4,9]. In contrast, other experimental studies have failed to convincingly demonstrate the true positive TCE in rodent hepatic tumor models [10,11].…”
Section: Dear Editormentioning
confidence: 55%
“…1D of Narita et al [1] and in animal results [3,4,9]. The most straightforward approach is to calculate the postcontrast tumor-to-liver contrast ratio (CR), i.e., CR = SI tumor /SI liver .…”
Section: Dear Editormentioning
confidence: 99%